DETERMINATION OF UROPEPSIN IN URINE IN IRON DEFICIENCY ANAEMIA IN EARLY CHILDREN AND ITS SIGNIFICANCE - Kholmuradova Zilola Ergashevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. WHO data according to, every 1.5 billion per year more than anemia with patients to list is taken, almost 50% of cases iron shortage with related to UNICEF’s Micronutrient Initiative iron shortage anemia to work of competence serious decline, mothers of death increase, child physical and mental to develop negative impact to show such as economic importance has was factors between dependency shows . This and iron shortage anemia diagnosis early in the making various kind diagnostic methods question In children blood in diseases urine in the composition uropipsin amount determination less learned because of , we iron shortage anemia there is in children him/her to determine current that We knew . The work purpose so , anemia weight to the level related in the case in urine uropepsin Definition . Materials and methods . From 1 to 3 years old was every kind severe iron deficiency anemia 42 children were examined . Stomach fermentative function in urine issued uropepsin amount with Pepsinogen stomach mucus on the floor working will be issued and to the blood decreased by 1% urine with uropepsin in appearance Research for morning issued from urine last second part taken, its amount and first and second pee between past time record The patient was in children in urine uropepsin amount anemia weight level into account received without Iron deficiency was detected . in anemia in urine uropepsin amount decrease was shown. Even light level uropepsin also in anemia amount in urine healthy was to children than much lower (P <0.001 ) was detected in urine uropepsin level study analysis this showed that his decrease anemia weight level increase parallel to . The lowest figures average and heavy level in anemia determined that is - up to 0.422 units per hour , ( normally 3.696 units per hour ). On average of the disease heavy at the level of 2.8 ± 0.51 units hour , and the norm is 7.46 ± 0.40 units organization Clinical recovery on time come , anemia with sick children’s in most cases 56.3% in urine uropepsin amount to normal values a little closer indicated , while in 43.7% of patients indicators normalization trend observed , but not completely to the norm did not come close . In the urine uropepsin of the composition normalization of the disease weight to the level related was : it is light at the level sick in patients complete restored if , average and especially heavy at the level sick in patients this indicator , norm relatively as little as possible saved.